Effects of Mycorrhiza, auxin and irrigation regimes on auchenorrhyncha (Hemiptera) complex damage in sorghum (Sorghum bicolor L.) - Iddrisu, Abdul Mumeen; Ozgen, Inanc (Springer Heidelberg, 2026)
Understanding how root health alongside hormonal metabolism affect crop-insect relationship under moisture stress is important for sustainable agriculture especially under the current global climatic condition. This study assessed the interactive effects of arbuscular mycorrhizal fungi (AMF), auxin (indole-3-butyric acid; IBA) and irrigation regimes on leaf damage caused by a complex of Auchenorrhyncha insects: Laodelphax striatellus, Cicadulina bipunctata, Psammotettix striatus and Balclutha punctate in Sorghum bicolor. A four-factor Randomized Complete Block Design (3 x 2 x 2 x 3) was implemented under controlled conditions, and insect feeding intensity was quantified as punctiform bite counts across top, middle and bottom leaves. ANOVA on log(1)(0)-transformed data revealed strong main and interaction effects, with the model explaining 96% of feeding variance (adjusted R-2 = 0.947). AMF inoculation on average consistently reduced total insect bites (approximate to 147 compared to 211 bites leaf(-)(1)), whereas auxin application significantly increased insect preference (with bite counts approximate to 212 compared to 146 bites leaf(-)(1)). Irrigation exerted a strong gradient effect, with the highest feeding under low moisture (approximate to 226 bites leaf(-)(1)) and the lowest under high irrigation (approximate to 132 bites leaf(-)(1)). Insect bite intensity followed a vertical canopy pattern (bottom > middle > top). Key interactions demonstrated that, AMF protection was maximized under medium-high irrigation. Secondly, auxin and drought synergistically amplified insect feeding. Moreover, AMF most strongly reinforced defense in the heavily attacked basal leaves. Heat-map visualization integrated these high-order interactions, highlighting that the combination AMF(-) + auxin(+) + low irrigation generated the greatest vulnerability, whereas AMF(+) + auxin(-) + medium irrigation minimized pest damage across the canopy. Overall, the findings show that Auchenorrhyncha feeding on sorghum is controlled by a multidimensional network of symbiosis, hormone balance and water status. Management strategies that optimize AMF colonization while avoiding hormonal overstimulation can substantially enhance plant robustness and suppress this pest complex under moisture stress conditions.
Keywords: Sorghum; Auchenorrhyncha; AMF; Auxin; Moisture stress